Effect of hydrophobicity on the water flow in carbon nanotube—A molecular dynamics study. Issue 4 (July 2018) - Esmaeilzadeh, Hamed; Su, Junwei; Charmchi, Majid; Sun, Hongwei
HIGHLIGHTS: The effect of hydrophobicity on the water flow in carbon nanotubes (CNTs) is studied using a molecular dynamics approach. The hydrophobicity was characterized by interaction-energy-coefficient (IEC). The static contact angles between water and carbon surface decreases with increasing the IEC. The hydrophobicity of CNT surface has a significant impact on the pressure drops of water flow in CNT. ABSTRACT: This work focuses on the study of the effect of hydrophobicity on the water flow in carbon nanotubes (CNTs) using a molecular dynamics (MD) approach for a wide range of potential applications such as water purification and high efficiency of nanofluid energy absorption systems (NEAS). The hydrophobicity between liquid water and surface of CNTs was characterized by interaction-energy-coefficient (IEC)—a parameter describing the energy interaction strength between water molecules and carbon atoms. It is shown that the static contact angles between water and carbon surface decrease from 155° to 44° when the values of IEC increase from 0.042 kJ/mol to 2.196 kJ/mol. In addition, the pressure drops in CNT became independent of IEC when the IEC value was higher than 1.192 kJ/mol for a given flow rate. It was found that the hydrophobicity of CNT surface has a significant impact on the pressure drop of water flow in the CNTs and MD method provides a quantitative evaluation of the impact. Graphical Abstract: This work focuses on the study of the effect of hydrophobicity on the water flow in carbon nanotubes (CNTs) using a molecular dynamics (MD) approach for a wide range of potential applications such as water purification and high efficiency of nanofluid energy absorption systems (NEAS). The hydrophobicity between liquid water and surface of CNTs was characterized by interaction-energy-coefficient (IEC)—a parameter describing the energy interaction strength between water molecules and carbon atoms. It is shown that the static contact angles between water and carbon surface decrease from 155° to 44° when the values of IEC increase from 0.042 kJ/mol to 2.196 kJ/mol. In addition, the pressure drops in CNT became independent of IEC when the IEC value was higher than 1.192 kJ/mol for a given flow rate. It was found that the hydrophobicity of CNT surface has a significant impact on the pressure drop of water flow in the CNTs and MD method provides a quantitative evaluation of the impact.